Surgical treatment in older patients with endometrial cancer: A retrospective study. (September 2022) - Luzarraga-Aznar, Ana; Teixeira, Natalia; Luna-Guibourg, Rocío; Español, Pia; Soler-Moreno, Cristina; Rovira, Ramon
Abstract: Introduction: Older patients (OP) diagnosed with endometrial cancer (EC) are less likely to receive an optimal surgical treatment compared with non-older patients (NOP). This undertreatment along with the presence of more aggressive tumours at diagnosis can explain the worse prognosis of EC in OP. There is limited evidence comparing perioperative outcomes between OP and NOP, and the benefit of applying complex procedures to OP is still controversial. The primary objective of the study was to compare intraoperative and postoperative complications between NOP and OP with EC that underwent primary surgery. Secondary objectives were to compare surgical management and survival rates. Methods: This is a retrospective single-centre observational study including women undergoing surgery for EC between 2010 and 2019. Patients were classified according to age as NOP (younger than 75 years) or OP (75 years or older). Basal characteristics and surgical outcomes of groups were compared using Chi-square, Fisher's exact tests, student T-tests or Mann Whitney tests. Kaplan Meier analysis was used to evaluate survival. Results: In total 281 patients underwent primary surgery for EC between 2010 and 2019 in our centre. At diagnosis, 184 patients were younger than 75 years while 97 were 75 and older. No differences were found in disease characteristics. Most of our patients (83, 3%) underwent laparoscopic surgery. Pelvic (58, 2% vs. 37, 1%, p = 0, 001) and para-aortic (46, 7% vs. 23, 7%, p < 0, 001) lymphadenectomies were performed more frequently in NOP compared with OP. Rates of intra-operative (6, 5% vs. 12, 4%, p = 0, 116) and post-operative (13, 0% vs. 20, 6%, p = 0, 120) complications were not statistically different between NOP and OP, and neither was the rate of severe complications according to Clavien-Dindo classification (5, 4% vs. 8, 2% of complications grade III-V respectively, p = 0, 387). The 5-year disease-specific survival (DSS) rate tended to be lower in the OP than in the NOP (74, 8% vs. 82, 5%, p = 0, 071). Considering only patients in whom complete surgical staging was performed, OP presented similar DSS to NOP, with comparable complication rate. Conclusions: OP do not present a significantly higher rate of perioperative complications compared to NOP. However, they underwent fewer lymphadenectomies and tended to present poorer DSS. Further studies are needed to standardize the surgical management of these patients. Highlights: Older patients with endometrial cancer, tend to undergo fewer lymphadenectomies compared to Non-Older patients. Surgical complications are not increased in Older patients undergoing surgical staging for endometrial cancer. Sentinel Lymph node dissection may lead to an improved lymph node staging in Older patients with endometrial cancer.